Estimating Price Discounts for Low-Quality Maize in sub-Saharan Africa: Evidence from Benin. (January 2016) - Kadjo, Didier; Ricker-Gilbert, Jacob; Alexander, Corinne
Highlights: Survey data from 360 smallholder farmers in Benin. Estimate price discounts for maize with different levels of insect damage. 10% increase in insect damage leads to 9% discount using stated preference, but 3% discount with revealed preference. Higher price discounts for damaged maize early postharvest period than lean period. Better storage technologies needed to incentivize production and storage of good quality maize. Summary: This article uses household data from Benin to estimate the extent that markets in sub-Saharan Africa discount damaged maize. Stated preference methods indicate that a 10% increase in insect damage results in a 9% maize price discount. However, revealed preference methods indicate that this discount is only 3%. Discounts are larger immediately after harvest than they are in the lean period when maize is scarce. Our results help explain why many smallholder farmers sell maize at harvest rather than making the effort to preserve grain of good quality for later in the season when it may fetch a higher price.